2009
DOI: 10.1158/1055-9965.epi-08-0972
|View full text |Cite
|
Sign up to set email alerts
|

Adult Height, Insulin, and 17β-Estradiol in Young Women

Abstract: Background: Adult height and insulin are thought to modify the development of breast cancer. However, little is known about the association between height and 17B-estradiol, a key factor in breast carcinogenesis, and whether insulin modifies such an association. Methods: Among 204 healthy women, ages 25 to 35 years, who participated in the Energy Balance and Breast Cancer Aspect I study, adult height (in centimeters) and fasting serum concentrations of insulin (pmol/L) were measured. 17B-Estradiol concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
3
13
0
Order By: Relevance
“…The association between higher levels of estradiol and higher body height in premenopausal women (20-40 years old) (Dorgan et al, 1995, Finstad et al, 2009) and in pubertal women (Pescovitz et al, 1985) was reported previously. In our studies, young women with above average body height had a higher estradiol level then women with below average body height.…”
Section: Are There Any Relations Between Body Height and Hormone Levesupporting
confidence: 69%
See 1 more Smart Citation
“…The association between higher levels of estradiol and higher body height in premenopausal women (20-40 years old) (Dorgan et al, 1995, Finstad et al, 2009) and in pubertal women (Pescovitz et al, 1985) was reported previously. In our studies, young women with above average body height had a higher estradiol level then women with below average body height.…”
Section: Are There Any Relations Between Body Height and Hormone Levesupporting
confidence: 69%
“…Estradiol targets mainly reproductive organs, but also stimulates bone growth during the "pubertal jump" (Creager, 1992). There are publications demonstrating a positive association of a higher estradiol level with a higher body height and body weight in premenopausal (Dorgan, 1995, Finstad, 2009) and fertile (De Pergola, 2006) woman, as well as an association of a higher estradiol level with lower WHR (Waist to hip ratio) value in premenopausal woman (Jasienska, 2004). WHR is an appropriate indicator of body fat content (Park et al, 2002;Suh et al;2002), which is widely used as a convenient index of abdominal obesity (Pouliot et al, 1994;Ross et al, 1992) and related metabolic syndrome (Hollmann et al, 1997).…”
mentioning
confidence: 99%
“…It included 204 healthy women aged 25-35 years, with regular menstrual cycles (length 22-38 days) [19,22].…”
Section: Methodsmentioning
confidence: 99%
“…They attended three scheduled visits during their menstrual cycle, after onset of the menstrual bleeding (first visit days 1-5, second visit days 7-12 and third visit days [21][22][23][24][25]. Anthropometric measurements were conducted with participants wearing light clothing and no footwear.…”
Section: Clinical Examinationmentioning
confidence: 99%
See 1 more Smart Citation